Comparative efficacy of topical 10% versus 5% tranexamic acid in treatment of women with melasma: a double-blind randomized controlled trial - Mawu, Ferra Olivia; Kapantow, Marlyn Grace; Pandaleke, Herry E. J.; Cahyadi, Alexandro Ivan; Togelang, Lidya; Tampi, Joan Alexandra; Christopher, Paulus Mario (Universa Medicina, 2024)
BackgroundMelasma is a highly prevalent chronic pigmentary disorder. The pathogenesis is unknown but melasma often occurs in photo-exposed areas, e.g., cheeks, upper lip, chin, and forehead. Tranexamic acid (TA), a plasmin inhibitor, aids in the inhibition of UV-induced plasmin activity and melanogenesis, making it a favorable therapeutic option for melasma. Tranexamic acid may be administered through various routes, e.g., topical. This study aimed to compare the efficacy of topical 10% versus 5% TA in women with melasma. MethodsThis double-blind randomized controlled trial included 16 females with epidermal type melasma who were randomized into two groups to receive either topical 10% TA (n = 8) or 5% TA (n = 8) applied twice daily for eight weeks. Prior to intervention and at 8 weeks after intervention, the intensity and extension of melasma were assessed based on melasma area and severity index (MASI) score and pigmentation score. ResultsMean MASI and pigmentation scores in both treatment groups were similar at base-line (p>0.05). The reduction in MASI and pigmentation scores in the topical 10% TA and 5% TA groups was similar and statistically not significant after 4 and 8 weeks of treatment (p>0.05). There were no drug-related adverse reactions or complications. ConclusionThis study demonstrated that topical 10% TA and 5% TA were effective in treating women with melasma. The utilization of topical 5% TA for melasma is a promising alternative therapeutic option without the need to increase the concentration of the formulation.